From diagnosis to treatment: exploring the mechanisms underlying optic neuritis in multiple sclerosis - Bin Tong; Xin Zhang; Haijian Hu; Huayi Yang; Xifeng Wang; Maolin Zhong; Fan Yang; Fuzhou Hua (Journal of Translational Medicine)
Abstract Multiple sclerosis (MS) is a chronic autoimmune disease affecting the central nervous system, commonly causing sensory disturbances, motor weakness, impaired gait, incoordination and optic neuritis (ON). According to the statistics, up to 50% of MS patients experience vision problems during the disease course, suffering from blurred vision, pain, color vision deficits, and even blindness. Treatments have progressed from corticosteroids to therapies targeted against B/T cells. This review comprehensively and systematically reappraises the diagnostic methods for visual impairment in MS patients. It also summarizes the most recent treatment approaches and effective medications for ON in MS. Finally, we examine the immunoinflammatory mechanisms that underlie lesions in the central nervous system in multiple sclerosis, in order to direct future investigations to confirm these mechanisms in the visual pathway.